Farmer Participants Perception on Development of Livestock Agribusiness Training in Temanggung District - M Eti Wulanjari; Trie Joko Paryono (Jurnal Ilmiah ESAI, 2011)
The objectives of this research were to know partisipants perception of the training development of livestock agribusiness towards training materials and training benefits. Training was held on 22-25 July 2009 with 30 respondents of all the training participants. The data analyzed by: 1) descriptive analyze, and 2) Spearman Rank Correlation to determine the relationship of variables x and y in an ordinal scale. The results showed that participants of the training have a positive perception of the training materials and training benefits. The respondent characteristic who perceive an important role in the training material is the education of respondentsÂ Key words:Â  perception, farmer, training